Bayesian Compressive Sensing for Ultra-Wideband Channel Models - Özgör, Mehmet; Erküçük, Serhat; Çırpan, Hakan Ali (Ieee, 345 E 47Th St, New York, Ny 10017 Usa, 2012)
Considering the sparse structure of ultra-wideband (UWB) channels, compressive sensing (CS) is suitable for UWB channel estimation. Among various implementations of CS, the inclusion of Bayesian framework has shown potential to improve signal recovery as statistical information related to signal parameters is considered. In this paper, we study the channel estimation performance of Bayesian CS (BCS) for various UWB channel models and noise conditions. Specifically, we investigate the effects of (i) sparse structure of standardized IEEE 802.15.4a channel models, (ii) signal-to-noise ratio (SNR) regions, and (iii) number of measurements on the BCS channel estimation performance, and compare them to the results of l(1)-norm minimization based estimation, which is widely used for sparse channel estimation. The study shows that BCS exhibits superior performance at higher SNR regions only for adequate number of measurements and sparser channel models (e. g., CM1 and CM2). Based on the results of this study, BCS method or the l(1)-norm minimization method can be preferred over the other for different system implementation conditions.
Keywords: Bayesian compressive sensing (BCS); IEEE 802.15.4a channel models; l(1)-norm minimization; ultra-wideband (UWB) channel estimation